Dukarr lakarama: Listening to Guwak, talking back to space colonization. (August 2020) - Mitchell, A.; Wright, S.; Suchet-Pearson, S.; Lloyd, K.; Burarrwanga, L.; Ganambarr, R.; Ganambarr-Stubbs, M.; Ganambarr, B.; Maymuru, D.; Maymuru, R.; ,
Abstract: Guided by the Yolŋu songspiral of Guwak, in this collaboratively written paper we argue that the extension of earth-based colonization into space disrupts and colonises the plural lifeworlds of many Indigenous people who have ongoing connections with and beyond the sky. Listening to Guwak, we speak back to promoters of space colonization who frame their projects as harmless according to four core understandings. First, they assume that there are no people or other beings Indigenous to what they think of as 'outer space', and that none of the Indigenous people or beings who also live on earth have travelled to or inhabited this space. Second, they assume that space is dead or non-sentient in itself, and that it is incapable of fostering life. Third, they understand that space is cleanly separated from earth, meaning that what happens in space has no effect on earth, or vice versa. Fourth, because of these three assumptions, they do not identify any ethical objections to occupying and exploiting space. We follow Guwak as she undermines each of these assumptions, by moving through and as Sky Country. These learnings emphasize the presence and role of Law, order and negotiation in Sky Country; the active, animate, agential presence of beings in Sky Country; the connectivity and co-becoming-ness of earth and sky; and the ethical obligations to attend to and care for and as Sky Country. We contend that the argument applies to many worlds that intimately connect with, extend into (or beyond) what Western sciences call 'outer space'. Indeed, we hope that in sharing Guwak we encourage broader conversations about Sky Country and its relations with other Indigenous worlds.